Analisis Yuridis Transplantasi Organ Ditinjau Dari Perspektif Undang-Undang No 17 Tahun 2023 Tentang Kesehatan - Aziz, Taufik; Efrila, Efrila; Suswantoro, Tri Agus (SENTRI: Jurnal Riset Ilmiah, 2025)
Organ transplantation is a surgical procedure intended to replace a completely damaged or non-functioning organ with healthy tissue obtained from a donor. This process, as regulated under Article 124 paragraph (1) of the Health Law, is conducted to cure certain medical conditions, restore essential bodily functions, and must be carried out solely for humanitarian purposes. Furthermore, Article 124 paragraph (3) prohibits any form of trade involving human organs or tissues, highlighting the ethical and legal concerns associated with commercialization. Therefore, understanding and analyzing the legal framework governing organ transplantation is of critical importance to ensure compliance with national regulations and uphold ethical standards in medical practice. This research adopts a normative legal approach, focusing on the analysis of laws and regulations. In Indonesia, legal aspects of organ transplantation are regulated by Law No. 1268/2001, and further supported by several ministerial regulations, including Minister of Health Decree No. 17 of 2023, No. 53 of 2021, and Ministerial Regulation No. 38 of 2016.